(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This article is a study of the evolution of political regimes in Kyrgyzstan, starting from the Soviet era and tracing their development to the present. The article examines the key stages of the political history of Kyrgyzstan, including the Soviet period, the transition to independence, political crises, and the formation of a modern political system. The author analyzes the factors that influenced the development of political regimes, such as ethnic and religious dynamics, the role of national leaders, and external influences. Also, the evolution of institutional structures and mechanisms of power, including elections and constitutional reforms, is considered.